[Gdańsk, Długi Targ 25, 26] [fot. Hubert Müller]. - Müller, Hubert (architekt) (2013)
Przedstawia kamienice nr 25, 26 przy ul. Długi Targ, widoczny wylot ul. Pończoszników i fragment Zielonej Bramy, 1943-1944.